Sub-nanometer depth resolution and single dopant visualization achieved by tilt-coupled multislice electron ptychography - Zehao Dong; Yang Zhang; Chun-Chien Chiu; Sicheng Lu; Jianbing Zhang; Yu-Chen Liu; Suya Liu; Jan-Chi Yang; Pu Yu; Yayu Wang; Zhen Chen (Nature Communications, 2025)
Abstract Real-space, three-dimensional imaging of atomic structures in materials science is a critical yet challenging task. Although scanning transmission electron microscopy has achieved sub-angstrom lateral resolution through techniques like electron ptychography, depth resolution remains limited to only 2 to 3 nanometers using single-projection setups. Attaining better depth resolution often requires large sample tilt angles and numerous projections, as demonstrated in atomic electron tomography. Here, we introduce an extension of multislice electron ptychography, which couples only a few small-angle projections to improve depth resolution by more than threefold, reaching the sub-nanometer scale and potentially approaching the atomic level. This technique maintains high resolving power for both light and heavy atoms, significantly enhancing the detection of individual dopants. We experimentally demonstrate three-dimensional visualization of dilute praseodymium dopants in a brownmillerite oxide, Ca2Co2O5, along with the accompanying lattice distortions. This approach can be implemented on widely available transmission electron microscopes equipped with hybrid pixel detectors, with data processing achievable using high-performance computing systems.